2008
DOI: 10.1002/jmri.21451
|View full text |Cite
|
Sign up to set email alerts
|

Automatic image‐driven segmentation of the ventricles in cardiac cine MRI

Abstract: Purpose: To propose and to evaluate a novel method for the automatic segmentation of the heart's two ventricles from dynamic ("cine") short-axis "steady state free precession" (SSFP) MR images. This segmentation task is of significant clinical importance. Previously published automated methods have various disadvantages for routine clinical use. Materials and Methods:The proposed method is primarily image-driven: it exploits the spatiotemporal information provided by modern 3Dϩtime SSFP cardiac MRI, and makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 34 publications
(87 reference statements)
0
46
0
Order By: Relevance
“…These works deal with different strategies for approaching the segmentation task, including image-driven algorithms [10][11][12][13], probabilistic atlases [14,15], fuzzy clustering [16], deformable models [17][18][19], neural networks [20], active appearance models [21,22], anatomical-based landmarks [23], or level set and its variations [24,25]. A comprehensive review of techniques commonly used in cardiac image segmentation can be found in Kang et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…These works deal with different strategies for approaching the segmentation task, including image-driven algorithms [10][11][12][13], probabilistic atlases [14,15], fuzzy clustering [16], deformable models [17][18][19], neural networks [20], active appearance models [21,22], anatomical-based landmarks [23], or level set and its variations [24,25]. A comprehensive review of techniques commonly used in cardiac image segmentation can be found in Kang et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the works on LV segmentation also show results for RV segmentation. These include image-based approaches like thresholding [28][29][30], pixel classification approaches [31,32], deformable models [33][34][35][36], active appearance models [27,37], and atlas based methods [19,23,38].…”
Section: Introductionmentioning
confidence: 99%
“…The best result reported was 2.06 0.58 mm (mean surface distance). Cocosco et al [39] validated their segmentation results using regression of segmented volumes and reported (left ventricle) and (right ventricle). Kurkure et al [29] reported a mean Dice number of 0.855 0.123 for ventricle segmentation from cine cardiac MR images.…”
Section: Performance Of the Proposed Frameworkmentioning
confidence: 93%